KEBERDAYAAN INDUSTRI KERAJINAN RUMAH TANGGA UNTUK PENGENTASAN KEMISKINAN DI PROVINSI BALI (Ditinjau dari Aspek Modal Sosial dan Peran Lembaga Adat) - Nyoman Yuliarmi; AAIN Marhaeni; IAN Saskara; Sudarsana Arka; L P Wiagustini (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2014)
The aim of this research is to analize 1) the impact of social capital on empowerment level of household craft industry in Bali Province, 2) the impact of social capital on traditional institution from its social, culture, and financial role for empowering household craft industry in Bali Province, and 3) the impact of traditional institution from its social, culture, and financial role on empowerment of household craft industry in Bali Province. Based on certain reason, this study was carried out in 5 regencies with poor family level I who has the biggest number of household craft industry unit, i.e., Badung, Karangasem, Bangli, Kelungkung, Tabanan, and Gianyar. The number of sample was 100. Data were collected through interview by using questionnaire. Technique of analysis was Equation Structural Modeling (SEM) with Partial Least Square (PLS). Based on result and discussion, it is concluded that 1) social capital was not influencedirectly the empowerment of household craft industry in Bali Province, 2) social capital influence social, culture, and financial role of traditional institution in endeavour to increase empowerment of household craft industry in Bali Province, and 3) social, culture, and financial role of traditional institution influence empowerment of household craft industry in Bali Province.